Effective Relationships for School College Partnerships, 1984-87, and Achieving Academic Excellence through School/College Partnerships, 1987-90. Qualitative Evaluations of the Curriculum Enhancement Projects Participating in the California Academic Partnership Program - Galligani, Dennis J.; California Academic Partnership Program ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This document contains two studies of California curriculum enhancement projects designed to develop academic partnerships between secondary and postsecondary institutions and improve the academic preparation of students. The first study provides a qualitative evaluation of 20 projects funded by the California Academic Partnership Program (CAPP) during the first funding cycle (1984-1987). It examines characteristics which contribute to effective partnerships, successful methods for achieving curriculum enhancement goals, methods for reaching specific CAPP project goals, and unintended outcomes. It also outlines recommendations for effective partnership relationships. The second study emphasizes CAPP's role in motivating students underrepresented in postsecondary education due to historical, economic, or geographic factors, and describes a set of 10 curriculum enhancement projects. This study's findings focus on effective administrative structures, promoting faculty-to-faculty interactions, enhancing school curriculum, communicating effectively, involving parents, sharing costs, and ensuring institutionalization. It also concludes with recommendations for effective partnership development. Appendices include California Assembly Bill 2398, lists of CAPP curriculum enhancement projects, and materials used in program evaluation. Contains 14 references. (GLR)
Availability: California State University Academic Publications Program, CSU Chancellor's Office, 400 Golden Shore, Suite 132, Long Beach, CA 90802 ($12).
ERIC Note: This document is part of a collection produced under the auspices of the California State University Institute for Teaching and Learning. The CSU/ITL, created in 1988, facilitates a 20-campus systemwide network of faculty affiliates in response to the demand for improved teaching and learning in the college classroom.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Bound Students; College Preparation; College School Cooperation; Cooperative Programs; Curriculum Development; Curriculum Enrichment; Educational Cooperation; Ethnic Groups; Higher Education; Institutional Cooperation; Intermediate Grades; Minority Groups; Program Development; Program Evaluation; Qualitative Research; Secondary Education; State Universities; Student Recruitment; Teamwork; California State University Inst for Teach Learn -- College Teaching and Learning Collection; California -- California State University; Reports, Evaluative